PEMBIAYAAN MURABAHAH DALAM PERBANKAN SYARIAH - Nasrulloh . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2004)
Today, Islamic Bank, or better known as Muamalat Bank has been an interesting phenomenon. The Islamic Bank has It's own system, including the financing system. This financing system is known as